Chemical Compounds and Bioactivity of Aqueous Extracts of Alibertia spp. in the Control of Plutella xylostella L. (Lepidoptera: Plutellidae) - Lucas L. S. Peres; Ana I. Sobreiro; Irys F. S. Couto; Rosicléia M. Silva; Fabricio F. Pereira; Silvia C. Heredia-Vieira; Claudia A. L. Cardoso; Munir Mauad; Silvana P. Q. Scalon; Sandra S. Verza; Rosilda M. Mussury (Insects, 2017)
Successive applications of insecticides to control Plutella xylostella L. (Lepidoptera: Plutellidae) have resulted in the emergence of resistant populations of this insect. A novel control measure for this target insect could be the use of botanical insecticides derived from plant tissues. Hence, we experimentally tested aqueous extracts of Alibertia edulis (Rich.), Alibertia intermedia (Mart.), and Alibertia sessilis (Vell.) K. Schum. found in the Brazilian savannah in order to investigate their potential to disrupt the life cycle of P. xylostella. Aqueous extracts of the leaves of A. intermedia and A. sessilis negatively affected the development of P. xylostella in all stages of the life cycle, prolonging the larval stage and causing mortality in the larval or pupal stages. Treatments with A. intermedia and A. sessilis extracts caused the lowest fecundity and the number of hatched larvae. The harmful effects of these aqueous extracts on the life cycle of P. xylostella may be attributable to the flavonoids and other phenolic compounds present in A. intermedia and A. sessilis. These aqueous botanical extracts are low in toxicity when compared to non-aqueous pesticides, and may emerge as an effective approach for control of populations of P. xylostella.